Preoperative Differentiation Between Malignant and Benign Ovarian Masses in Patients with Normal CA-125 Levels - Ebru Ersoy; Aytekin Tokmak; Ali Ozgur Ersoy; Özlem Evliyaoğlu; Esma Sarıkaya (Medical Network, 2016)
OBJECTIVE: We aimed to determine the diagnostic values of some clinical and ultrasonographic features for predicting ovarian malignancies in patients with normal serum CA-125 levels. STUDY DESIGN: All of the 84 patients who were diagnosed with ovarian malignancy and 168 patients with benign adnexal mass had normal CA-125 levels, and recruited as study and control groups, respectively. Individual characteristics, ultrasonographic features, and risk of malignancy index (RMI) values of the groups were compared retrospectively. RESULTS: The ages, mean postmenopausal period of the postmenopausal women in the malignant group were significantly higher than the benign group. Nulliparity rates were similar between the two groups. The number of postmenopausal patients was significantly higher in the malignant group. Median cyst diameter and RMI values were significantly higher, and bilaterality and presence of solid area were more frequent in this group. Logistic regression model showed that ovarian cysts larger than 8 cm [Odds ratio (OR): 7.012; p<0.001; 95% Confidence interval (CI): 3.463-14.198], presence of solid area within the cyst [OR: 7.43; p<0.001; 95% CI: 3.799-14.532], and postmenopausal state [OR: 2.893; p=0.027; 95% CI: 1.129-7.412] were found to be significant factors to predict malignancy. CONCLUSION: Ovarian cysts larger than 8 cm, presence of solid area within the cyst, and postmenopausal status are the most important risk factors for ovarian malignancies in these patients with normal CA-125 levels.